Think Globally, Act Locally? Evaluating Boston Climate Projects’ Community Engagement - Gallo, Ava; Aldrich, Daniel P. (Human ecology : an interdisciplinary journal, 2024)
Successful climate change mitigation, adaptation, and transformation will require a balance of bottom-up, community-led planning and engagement with top-down resource deployment. While many non-governmental organizations (NGOs), civil society groups, and local agencies argue that they work closely with residents, especially on plans to manage extreme weather events and climate change, the degree to which local, urban-based climate projects engage with coastal communities remains an open question. Using interviews with nearly 20 project managers, local planners, and decision makers along with site visits to and archival research on three core projects in Boston, we evaluate the degree to which residents participate, plan, and engage. Despite being heralded by some observers as truly participatory, we found that none of the projects achieved the highest levels of participation possible seen in other community led projects. Further, none of the projects achieved consistent scores on the three evaluation criteria: equity, efficacy, and efficiency. This gap between rhetoric and reality must be closed if Boston and other vulnerable, coastal cities wish to build more equitable ways of managing challenges like climate change.